Evolution of Modern Zoology (The International Journal for Scientific Research, 2023)
Technology has contributed to the development of zoology, and the electron microscope has played an important role in many biological discoveries, as have oscilloscopes Binary isotopes, radiometry, digital photography and satellite images, PCR and DNA, and GPS systems, computers, and many of the technologies that worked on Progress in research fields in various branches of zoology has even contributed to finding solutions to some of the problems facing the environment in order to develop terrestrial and marine resources and preserve biodiversity It was the discovery and identification of Mendelian genetics, the structure of DNA, the code, instinct and animal behaviour Primitive and hybrid species, parthenogenetic forms of life, and new, previously unknown kingdoms of chemomorphology all had a positive impact on the development of zoology This paper discusses the development of zoology in the modern era. What distinguishes zoology is its impact on environmental balance and diversity preservation issues Organisms, ranging from restriction enzymes, the discovery of cloning, genetic engineering, and genetic control of decomposition states. Understanding metabolic pathways supports the need to address these topics with careful review, as we will see in this paper.
Keywords: Zoology; Electron Microscope; Biological Discoveries; Oscilloscopes Binary Isotopes; Radiometry; Digital Photography; Satellite Images; PCR; DNA; GPS Systems; Computers; Animal Behaviour; Primitive and Hybrid Species; Parthenogenetic Forms